Recht finding of the Constitutional Court In the perspective of the rule of law and democracy (Study of the Decision of the Constitutional Court of the Republic of Indonesia, Number: 90/PUU-XXI/2023) - Daud Yaferson Dollu; Yosua Pepris Karbeka (Dynamics of Politics and Democracy, 2025)
Purpose: As a state of law, the demand to produce quality laws in Indonesia is very necessary and must not contradict the 1945 Constitution. All regulations formed must be subject to the Constitution. However, the formation of laws and regulations under it often contradicts the constitution and is challenged in the Constitutional Court. One example is a lawsuit against Law Number 7 of 2017 concerning General Elections, Article 169 letter q, which later issued decision Number 90/PUU-XXI/2023. This paper aims to describe the act of legal discovery through Constitutional Court rulings as a pillar of the state of law and democracy. Research methodology: This research uses normative legal research, which is doctrinal or theoretical legal research, applying statutory, case, historical, and conceptual approaches. Results: The findings concluded that the Constitutional Court was right in its decision to amend Article 169 letter q of Law Number 7 of 2017 concerning General Elections, in order to uphold the concept of the rule of law and democracy in Indonesia. Conclusion: The ruling of the Constitutional Court demonstrates its role as the guardian of the Constitution, ensuring that laws align with constitutional principles and reinforcing democratic values. Limitations: The limitation of this research lies only on the aspect of legal discovery authority by the Constitutional Court. Contribution: This study contributes to strengthening the authority of the Constitutional Court in the future in line with the development of the times.